1994
DOI: 10.1007/bf00042588
|View full text |Cite
|
Sign up to set email alerts
|

The dual boundary element method for thermoelastic crack problems

Abstract: A boundary element formulation, which does not require domain discretization and allows a single region analysis, is presented for steady-state thermoelastic crack problems. The problems are solved by the dual boundary element method which uses displacement and temperature equations on one crack surface and traction and flux equations on the other crack surface. The domain integrals are transformed to boundary integrals using the Galerkin technique. Stress intensity factors are calculated using the path indepe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
39
0
2

Year Published

1998
1998
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 105 publications
(49 citation statements)
references
References 17 publications
8
39
0
2
Order By: Relevance
“…In Tables III-VI, the SIFs are compared with those of [35], reported in the handbook [1], and those of [5]. Following …”
Section: Rectangular Plate With An Inclined Crackmentioning
confidence: 99%
See 2 more Smart Citations
“…In Tables III-VI, the SIFs are compared with those of [35], reported in the handbook [1], and those of [5]. Following …”
Section: Rectangular Plate With An Inclined Crackmentioning
confidence: 99%
“…It is observed that the mesh density and the radius enrichment are sufficiently large since no oscillation due to the blending effect [30] is apparent on these plots. In Table II, the SIFs are compared with those of [34], reported in the handbook [1], and those of [5], obtained by a dual boundary element method. The first set of boundary conditions induces a pure sliding mode (mode II) at the tips and the second set a pure opening mode (mode I).…”
Section: Square Plate With a Centre Crackmentioning
confidence: 99%
See 1 more Smart Citation
“…8 Incorporation of this temperature/¯ux near-tip behaviour has been proved to be essential in thermal fracture analysis. 9,10 Near-tip stress and¯ux distributions, using the ®rst-order eigenfunction expansion method, are where " s ij , i, j 1Y 2, are the stress tensor components and K is the generalized intensity factor vector, given in the Appendix; p yi are the heat¯ux vector components, and functions F i (j) are described in the Appendix. In the above equations the overbar denotes that variables are considered in the local co-ordinate system ( "…”
Section: Introductionmentioning
confidence: 99%
“…Em problemas termoelásticos as aplicações são encontradas em Prasad et al (1994Prasad et al ( , 1996.…”
Section: O Mec No Contexto Da Teoria Da Elasticidade E Da Mecânica Daunclassified